KOMUNIKASI TERAPEUTIK TERHADAP TINGKAT KECEMASAN PASIEN SEBELUM DILAKUKAN ANESTESI REGIONAL - Verdiansyah, Rio (JURNAL MEDIA KESEHATAN, 2013)
The purpose of this study was to determine the effect of therapeutic communication to the patient's level of anxiety prior to regional anesthesia. The type of research is the pre-experimental design using one-group pretest-posttest. Sampling techniques accidental sampling of 30 samples. Data analysis was performed using Univariate and Bivariate analysis with paired t-test test on a5%. The results showed that there were differences in the mean levels of anxiety before and after therapeutic communication and there is a significant decrease in the mean levels of anxiety before and after therapeutic communication. In patients before surgery with regional anesthesia in the operating room RSUD.Dr.M.Yunus Bengkulu (P = 0.000).